Report of the Task Force Tariff Setting for PPP Projects in Major Ports - Planning Commission (Planning Commission, 2009)
The maritime sector presently carries 70 per cent by value and 95 per cent by volume of India's trade. The cargo handled by Indian ports is expected to rise from 720 MMT in 2007-08 to 1009 MMT in 2011-12. of which the Major Ports controlled by the Central Government would account for an increase from a level of 519 MMT in 2007-08 to 708 MMT in 2011-12. This will require a significant effort for creating additional capacity to meet the traffic demand. The Committee on Infrastructure, chaired by the Prime Minister, therefore, decided that following the successful experience of Public Private Partnerships (PPPs) in operating berths at Major Ports, and in order to maximise the inflow of private capital new berths at Major Ports would be constructed primarily through the PPP mode.
Planning Commission Government of India
Planning Commission Government of India